Strengthening of RC Beams Using Externally Bonded Fibre Reinforced Polymer Composites. (June 2018) - Nayak, A.N.; Kumari, A.; Swain, R.B.
Abstract: An experimental study is presented on the behaviour of reinforced concrete (RC) beams retrofitted externally with glass fibre reinforced polymer (GFRP) fabrics. Out of ten beams, one beam without GFRP and nine beams wrapped in various lay-up patterns with one, two, three and four layers of GFRP fabrics have been tested for flexure under two-point loading. Loads corresponding to the first crack/delamination and ultimate failure of the beams have been recorded and types of failure have also been observed. Load versus deflection graphs have been plotted at salient locations of beams. Thereafter, a critical discussion has been made with respect to increase in the flexural strength of retrofitted beams as compared to the control beam in order to explore the optimal use of GFRP fabrics for strengthening the RC beams. In addition, a design proposal has been developed in extension to IS: 456-2000 to predict the ultimate design strength of RC beams strengthened with fibre reinforced polymer (FRP) fabric sheets. Thereafter, the values of the experimental flexural strength of the strengthened RC beam have been compared with the corresponding values of design flexural strength computed from present formulation and ACI: 440-2R-08 for its validation. The results obtained from the present experimental study show that flexural strength of the strengthened RC beams increases with increase in number of layers for all lay-up patterns. However, the beams wrapped with two layers GFRP fabrics in the tension face and half of the both sides below neutral axis show superior performance with respect to flexural strength, ductility and economy. Highlights: Flexural strength increases with increase in the number of GFRP layers. Failure mode changes from ductile to brittle with increase in the number of GFRP layers. Development of design proposals to predict flexural strength Comparison of experimental flexural strength with predicted ones from various design proposals